Performance Improvement of Air-cooled Battery Thermal Management System using Sink of Different Pin-Fin Shapes - O. Miracle Oyewola; A. Andrew Awonusi; O. Saheed Ismail (Emerging Science Journal, 2022)
One of the most important influences on battery safety, capacity, and cell ageing is heat generation and temperature inhomogeneity, which cause unbalanced ageing, resulting in cell performance decline. A well-developed temperature management module is required to avoid such undesirable actions. In this study, an air-cooled temperature management module was developed by coupling a unique heat sink of different pin-fin geometries/shapes to prismatic Li-ion cells and a 3D transient analysis was conducted to simulate the cooling performance of this heat sink under the effect of inlet airflow velocities and temperatures at a discharge rate of 2C for three cases. The results in the form of maximum temperature and temperature homogeneity inside the battery were derived and compared to the commonly used circular pin-fin heat sink. The overall result indicates that case 2, which consists of uniform height, shows better promise than others, taking into consideration the geometry employed. After 600 s and at a constant inlet air velocity of 0.412 m/s across a range of 20 oC to 35 oC, it was found that this heat sink performed better, providing an average of 1.87% and 1.93% improvement in temperature homogeneity and battery maximum temperature, respectively. Also, at a constant inlet air temperature of 27 oC across the range of inlet air velocity of 0.206 m/s to 0.824 m/s, this heat sink provides an average of 1.77% and 0.27% improvement in temperature homogeneity and battery maximum temperature, respectively. Doi: 10.28991/ESJ-2022-06-04-013 Full Text: PDF